Strategies for Maintaining Household Harmony from the Perspective of the Teachers' Council - Siti Afiqoh (Divisi Penelitian dan Pengabdian Masyarakat Yayasan Cerdas Pedia Indonesia, 2026)
Every married couple must expect a harmonious and peaceful household life, but on the way, there are not a few tests that must be faced, both from within and outside the household. One external factor that often triggers relationship breakdown is negative interference from other parties. Therefore, the right strategy is needed to maintain harmony, such as maintaining good communication, mutual understanding, and mutual respect. This research is an empirical legal study with a qualitative descriptive approach conducted at the Darussalam Islamic Boarding School, by exploring the perspective of the board of teachers regarding strategies to maintain household harmony. The teachers in the pesantren are considered as figures who deserve to be role models because of the breadth of religious knowledge they have. The results showed that household harmony can be maintained well if couples are able to understand each other, be wise in filtering information from outside, and make communication the main key in solving problems that arise in the middle of household life.